EPILEPSIES WITH PYREXIAL REMISSIONS - L. V. Shalkevich (Русский журнал детской неврологии)
The course of epilepsies with reducing of number and severity of seizures due to increase of body temperature is described. There are 14 children with these epilepsy features are made as an example. Possible mechanisms of this process are assumed. The different mechanism of hyperthermia action on febrile seizures, Dravet syndrome, generalized epilepsy with febrile seizures plus are discussed. The main features ofepilepsies with pyrexial remissions are circumscribed with their rate. Possible hereditary factors of SCN1A mutations are supposed.